A yellow fluorescent protein-based assay for high-throughput screening of glycine and GABAA receptor chloride channels. - Kruger, W; Gilbert, Daniel; Hawthorne, R; Hryciw, DH; Frings, Stephan; Poronnik, P; Lynch, JW (Neuroscience Letters, 2005)
There is a significant clinical need to identify novel ligands with high selectivity and potency for GABA(A), GABA(C) and glycine receptor Cl- channels. Two recently developed, yellow fluorescent protein variants (YFP-I152L and YFP-V163S) are highly sensitive to quench by small anions and are thus suited to reporting anionic influx into cells. The aim of this study was to establish the optimal conditions for using these constructs for high-throughput screening of GABA(A), GABA(C) and glycine receptors transiently expressed in HEK293 cells. We found that a 70% fluorescence reduction was achieved by quenching YFP-I152L with a 10 s influx of I- ions, driven by an external I- concentration of at least 50 mM. The fluorescence quench was rapid, with a mean time constant of 3 s. These responses were similar for all anion receptor types studied. We also show the assay is sufficiently sensitive to measure agonist and antagonist concentration-responses using either imaging- or photomultiplier-based detection systems. The robustness, sensitivity and low cost of this assay render it suited for high-throughput screening of transiently expressed anionic ligand-gated channels.